DETERMINAN LINGKUNGAN FISIK DAN SOSIAL EKONOMI DENGAN KEJADIAN TUBERKULOSIS PARU DI KOTA BUKITTINGGI: PENDEKATAN STUDI KASUS-KONTROL - Eka Budi Satria; Harisnal Harisnal; Cory Febrina; Cici Apriliani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Tuberculosis (TB) is a major infectious disease in Indonesia, with the incidence in Bukittinggi City increasing to 335 per 100,000 population by 2023. This study aims to analyze the multidimensional environmental determinants (physical, socio-cultural, economic, and access to control programs) of TB incidence using a spatial approach. This study is an observational analytical quantitative study with a case-control design. The sample consisted of 110 respondents (55 cases of pulmonary TB patients and 55 healthy controls), selected through purposive sampling for cases and random sampling for controls, with matching based on age, gender, and neighborhood unit (RT). Data collected through interviews, observations, and secondary data from the 2024 SITB period were analyzed using univariate, bivariate (chi-square, OR, 95% CI), and multivariate (backward Wald logistic regression) methods using SPSS. The results showed that the dominant determinants were inadequate home ventilation (p=0.002; Exp β=3.49) and poverty status (p=0.041; Exp β=2.58). Other factors such as poor air quality, limited access to sunlight, and stigma also contributed significantly to the bivariate analysis. TB control requires cross-sectoral interventions focused on improving home ventilation and poverty alleviation to support TB elimination at the local level by 2030.Keywords: Tuberculosis; environmental determinants; home ventilation; poverty; case-control; Bukittinggi